Outcomes and Risk Factors Associated with Clostridium difficile Diarrhea in Hospitalized Adult Patients. (25th May 2015) - Larentis, Daniela Zilio; Rosa, Regis Goulart; dos Santos, Rodrigo Pires; Goldani, Luciano Zubaran
Abstract : Background . The epidemiology of Clostridium difficile infection has changed over time. Therefore, it is essential to monitor the characteristics of patients at risk of infection and factors associated with poor prognosis. Objective . To evaluate factors associated with C. difficile infection and with poor prognosis in those with documented C. difficile colitis. Methods . A retrospective case-control study of 75 patients with documented C. difficile colitis and 75 controls with hospital-acquired diarrhea of other causes. Stepwise multiple logistic regression was used to identify factors associated with C. difficile infection among patients with hospital-acquired diarrhea. Results . Previous antibiotic treatment (odds ratio (OR), 13.3; 95% confidence interval (CI), 1.40–126.90), abdominal distension (OR, 3.85; 95% CI, 1.35–10.98), and fecal leukocytes (OR, 8.79; 95% CI, 1.41–54.61) are considered as predictors of C. difficile colitis; anorexia was negatively associated with C. difficile infection (OR, 0.15; 95% CI, 0.03–0.66). Enteral tube feeding was independently associated with a composite outcome that included in-hospital mortality, intensive care unit admission, and treatment failure (OR, 3.75; 95%CI, 1.24–11.29). Conclusions . Previous antibiotic use and presence of fecal leukocytes in patients with hospital-acquired diarrhea are associated with C. difficile colitis and enteral tube support with complications associated with C. difficile colitis.